SJRMC; Let’s Continue - Muhammad Khurram, Muhammad Khurram (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
The aim of undergraduate medical education is to produce altruistic, knowledgeable, skillful, and dutiful doctors who are well versed with medicine.1 Reliance on scientific evidence for better patient management is mandatory. The medical students should thus be well versed with research.2 In Pakistan, medical research has been divisible into compulsive, interest related, institutional policies/ culture guided, and contributory/ collaborative types. Forced research is commonest of all. It is done as; 1) part of post graduate training, 2) requirement for a job, and 3) promotion etc.3 Research by interest is conducted by those who want to pursue career or as additional concern. Institutional policies and culture promotes research by regulations and competition respectively. Collaborative research is done with the help and funding of other institutes and organizations in order to reach new conclusions.4